Accident data study in support of development of autonomous emergency braking test procedures - James Lenard; Russell Danton (2010)
There is currently considerable interest in the development of physical test procedures for autonomous braking systems and one consideration is that the test conditions should be realistic, i.e. they should resemble or have a known relationship to the circumstances under which real road accidents occur. In this context, the aim of the work presented in this report is to describe typical circumstances for pedestrian, rear-end and head-on impacts based on British accident data. The scope of this work is limited to the description of accident data and although this report is intended as a contribution to the development of test conditions, it contains no discussion of how the results from the accident data should be used for this purpose. (...continues)